Site-directed mutations in a highly conserved region of Bacillus thuringiensis delta-endotoxin affect inhibition of short circuit current across Bombyx mori midguts. - Chen, X J (1993)
Bacillus thuringiensis delta-endotoxins (Cry toxins) are insecticidal proteins of approximately 65 kDa in the proteolytically processed and active form. The structure of one of these toxins, CryIIIA, has been determined by Li et al. [Li, J., Carroll, J. & Ellar, D. J. (1991) Nature (London) 353, 815-821] and contains three domains. It is believed that other delta-endotoxins adopt similar three-dimensional structure. Li et al. proposed that the first domain is the membrane pore-forming domain. Previous work from our laboratory has shown that the second domain is the receptor binding domain, but the function of the third domain is unclear. Site-directed mutagenesis was used to convert the "arginine face" of one of five highly conserved regions, QRYRVRIRYAS of CryIAa (residues 525-535), to selected other residues. This sequence corresponds to the beta-sheet 17 of CryIIIA in the third domain. Mutations in the second and third arginine positions resulted in structural alterations in the protein and were poorly expressed in Escherichia coli. Toxins from genes mutated to replace lysine for the first and fourth arginines were unaltered in expression and structure, as measured by trypsin activation, CD spectra, and receptor binding, but were substantially reduced in their insecticidal properties and inhibition of short circuit current across Bombyx mori midguts. It is proposed that this region plays a role in toxin function as an ion channel.